Social Minds Theory: How the Heroine in Trifles Get Away With Crime (Asian Journal of Social Science Studies, 2022)
Trifles is one of the outstanding representative works of feminist playwright Susan Glasper. Most of the previous studies on this play were limited to the field of dramatic performance or its feminist theme, but few scholars paid attention to the social minds in this play from the perspective of narrative. Starting from the point of social group thinking, this paper attempts to discuss how the author managed to help the criminal heroine get away with her crime of murder and eventually reveals the theme of rebellion against male hegemony and patriarchal exploitation, which utilizes social ideology of male supremacy among the society, the intermental thought between the two female characters in the drama and the collective thought between the inside characters and the outside audience.